2015
DOI: 10.1161/strokeaha.115.008694
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in Young Adults With Ischemic Stroke

Abstract: Background and Purpose— Cancer is a risk factor for ischemic stroke. Little is known about cancer among young adults with ischemic stroke. We studied the frequency of cancer and its association with long-term risk of death among young patients with first-ever ischemic stroke. Methods— 1002 patients aged 15 to 49 years, registered in the Helsinki Young Stroke Registry, and with a median follow-up of 10.0 years (interquartile range 6.5–13.8) after stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 27 publications
4
41
0
Order By: Relevance
“…218 Although it did not reach statistical significance, the young stroke patients had a higher rate or cardioembolic strokes, also after adjusting for patent foramen ovale (PFO). 218 Furthermore, Finelli et al portrayed DWI-findings in patients with stroke and cancer, where 75 % of the patients with embolic appearing infarctions actually had emboli of no detected source. 219 Clinically, if patients have embolic appearing strokes and report symptoms that indicate a possible AF such as palpitations, even without ECG findings, they might be classified as cardioembolic.…”
Section: Risk Factors -Conventional or Distinctive?mentioning
confidence: 95%
See 3 more Smart Citations
“…218 Although it did not reach statistical significance, the young stroke patients had a higher rate or cardioembolic strokes, also after adjusting for patent foramen ovale (PFO). 218 Furthermore, Finelli et al portrayed DWI-findings in patients with stroke and cancer, where 75 % of the patients with embolic appearing infarctions actually had emboli of no detected source. 219 Clinically, if patients have embolic appearing strokes and report symptoms that indicate a possible AF such as palpitations, even without ECG findings, they might be classified as cardioembolic.…”
Section: Risk Factors -Conventional or Distinctive?mentioning
confidence: 95%
“…Given the strong association between cancer-related stroke and poor clinical outcome, it is not surprising that the same patients also have an increased mortality. 105,218 In paper I we found that stroke patients with prior cancer had a double risk of death compared to other stroke patients. In paper III we did not study the mortality of the patients, but we saw that the patients with active cancer had a lower mean cholesterol level.…”
Section: Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Although the two studies were based on the long-term follow up results, patients comorbid with cancer were associated with higher mortality among the ischemic stroke patients. 19,20 In active cancer patients, the risk of HT, sICH and mortality were all increased with the use of rt-PA, not by endovascular therapy. Analyzing the patients who received IV thrombolysis only, not only the mortality rate in patients with active cancer, the proportion of cerebral hemorrhage were also higher than the patients without cancer.…”
Section: Journal Of Neurosonology and Neuroimagingmentioning
confidence: 99%